Synthetic Approaches to Chiral Non-C2-symmetric N-Heterocyclic Carbene Precursors - Czerwiński, Paweł J.; Michalak, Michał (Synthesis, 2019)
N-Heterocyclic carbenes and their metal complexes have found applications in many organic transformations. Apart from the privileged C2-symmetry present in modern enantioselective catalysis, ligands bearing C1-symmetry have witnessed growing attention due to the better control of process stereoselectivity in many cases. The present review summarizes, for the first time, the seminal synthetic efforts for the preparation of N-heterocyclic carbene precursors exhibiting C1-symmetry. The well-established methods will be discussed in the light of recent achievements, giving a direct opportunity for comparison of the existing methods, and simultaneously a chance to find the best synthetic pathway for the ideal chiral ligand.1 Introduction2 Five-Membered Rings2.1 Five-Membered Saturated (Imidazolinium) Ring2.1.1 Amino Alcohol Derivatives2.1.2 Amino Acid Derivatives2.1.3 Amine and Diamine Derivatives2.2 Five-Membered Unsaturated Ring2.2.1 Cyclization Strategy2.2.2 Functionalization of the Existing N-Imidazole Ring3 Triazolium Salts3.1 Substitution in Oxadiazolium Salts3.2 Lactam-Derived Triazolium NHC (The Leeper and Knight Methodology)3.3 Monoterpenoid-Derived NHC Triazolium Salts3.4 Modifications of the Existing Triazole Ring4 Thiazole-Derived Salts4.1 Cyclization of a Thiazolium Ring4.2 Modifications of the Existing Thiazole Ring5 Summary and Outlook
Keywords: chiral N-heterocyclic carbenes; non-C2-symmetry; amino alcohols; diamine; synthetic methodology